Reception: on auditory / sculptural relations in public space (Palíndromo, 2025)
Public space is a field where the values of democracy manifest themselves in direct proximity to certain anarchic conditions. It is the interrelationship between art and life, where society is revealed and built in shared spaces. What kind of relationship does a reactive sound space generate or question in relation to the listening public? In what context and in what way does the work have a sound memory? What does the place and the interactive proposal symbolize, with pure acoustics transferring time and space to sound? What motivates us to measure and define space is an essential desire that accompanies the impulse to reflect and ask questions. This equation can also be related between sculpture in the expanded field and the analysis of sound, about its particular impact on space.
Keywords: Sound Sclupture; Public Space; Aural Architecture; Sound Art; Soundscape